Energy characterization of residential and office buildings in a tropical location - Jorge Cárdenas-Rangel; German Osma-Pinto; Julián Jaramillo-Ibarra (Heliyon, 2023)
Governments have established regulations to reduce energy consumption and polluting gas emissions from buildings. In Colombia, the government issued Resolution 0549 in 2015, a regulation that imposed savings percentages on different types of buildings. Builders have had to improve their designs to meet this standard. However, this task requires a detailed understanding of the energy behaviour of buildings. In the absence of follow-up data, this study performed energy characterisations of a group of 20 residential and office buildings located in a tropical climate using DesignBuilder software. The simulations show a notable influence of plug-in loads on energy consumption as well as favourable thermal comfort conditions for all categories except for the low-income category. Solar radiation through windows is the largest source of heat in buildings. Additionally, the study shows the impact of a set of energy-saving measures on energy consumption. The results of this study can help designers reduce the energy consumption of tropical buildings and/or meet energy performance standards.